O prozie Brunona Schulza w teatrze - Tarnowska, Balbina (Załącznik Kulturoznawczy, 2021)
Due to the many unsuccessful theatrical adaptations of Bruno Schulz’s short stories, it is customary to say that his prose is ‘non-stage’. The reason for the failures of these adaptations lies not in the literary original, but in the specific methods of staging. Directors and adapters often repeat similar mistakes. Not all theatrical realizations based on work of Schulz are bad, there are also highly rated ones. There are two ways the adapter could take to show this prose in the theatre: capture the ‘spirit of the original’ or use the text as an inspiration.